EFFECT OF SILYMARIN ON INTESTINAL ALKALINE PHOSPHATASE LEVEL IN A RAT MODEL OF TYPE 2 DIABETES MELLITUS: STREPTOZOTOCIN AND HIGH-FAT DIET TREATED WISTAR RATS - V, Lalitha; T, Sivakumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This research elucidated the role of silymarin on intestinal alkaline phosphatase (IAP) level in type 2 diabetic rats. Methods: The type 2 diabetes mellitus was induced by a high-fat diet (HFD - 58% calories fat) for 2 weeks, and rats were intraperitoneally injected with streptozotocin (STZ) 35 mg/kg. Wistar rats were divided into four groups. Group I served as a non-diabetic (normal), Group II served as diabetic, Group III diabetic animals treated glibenclamide 600 Î¼g/kg for 14 days, and Group IV diabetic animal treated with glibenclamide and silymarin 50 mg/kg/twice/d for 14 days. At the end of the study, blood glucose, lipid profile, and IAP level were measured. Results: A significant decrease in IAP, elevated levels of blood glucose, and lipid profile was seen in diabetic rats when compared with normal. The silymarin treatment showed a significant increase in IAP level, a significant reduction in glucose and lipid profile than diabetic rats. Conclusion: The present study concludes that silymarin treatment enhances the IAP levels which protect against hyperglycemia, hyperlipidemia, and vascular complications in diabetic rats.